Interactive Arabic Language Learning: Enhancing Al-Arabiyah Baina Yadaik through Articulate Storyline - Yuliyanti, Silviya; Fauji, Imam (Indonesian Journal of Islamic Studies, 2024)
This study aims to develop instructional material for Al-Arabiyah Baina Yadaik's book As-Sakan utilizing Articulate Storyline. Employing the Research and Development (RnD) methodology, the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) is utilized for systematic development. Data collection techniques encompassed observation, interviews, expert validation, teacher and student questionnaires, as well as documentation. The material expert assessment yielded an average of 88%, indicating high suitability. Media experts also deemed the material highly feasible, scoring an average of 97%. Arabic teachers' response averaged at 97%, affirming its appropriateness. Moreover, grade 10 students achieved an impressive average score of 97.16%. Expert validations and user feedback demonstrate that this interactive learning medium, rooted in Articulate Storyline, is highly effective for Arabic language education, offering a promising avenue for enhanced learning experiences. Highlight: Methodological Approach: This study employs the Research and Development (RnD) methodology, leveraging the systematic ADDIE model for the development of instructional material, ensuring a structured and effective process. Comprehensive Data Collection: The research utilized diverse data collection techniques including observation, interviews, expert validation, and questionnaires from both teachers and students, as well as thorough documentation, ensuring a holistic assessment of the developed material. High Suitability and Effectiveness: Expert assessments, media experts' evaluations, and positive responses from Arabic teachers and grade 10 students collectively demonstrate the high suitability and effectiveness of the interactive learning medium created with Articulate Storyline, promising an enriched learning experience in Arabic language education Keyword: Instructional Material, Al-Arabiyah Baina Yadaik, Articulate Storyline, Research and Development, ADDIE Model